(untitled) (Research, Society and Development, 2021)
Objective: To analyze tuberculosis (TB) cases under the Directly Observed Treatment (TDO) regime in Porto Velho-RO between 2010 and 2017. Method: Descriptive, cross-sectional study with a quantitative approach, based on a survey of records of sociodemographic and clinical variables in the Information System for Notifiable Diseases and analyzed through frequency distribution, after meeting the ethical precepts. Results: A total of 3,738 cases were reported, of which 359 (9.6%) underwent the DOT, whose mean age was 36.2 years (sd = ± 16.5). Most were male (67.7%), mixed-race/color (75.0%), five to eight years of education (23.1%), lived in the urban area (84.6%), clinical form pulmonary (88.3%), new case (72.7%), suspected TB X-ray (75.7%), positive sputum smear microscopy (63.2%), negative HIV (53.7%), sputum smear microscopy for monthly control not performed, mean treatment time of 165.09 days (SD= ±88.92), low cure rate (61.3%) and high for dropout (20.6%), transfer (14.8%) and death (2.5%). Conclusion: It is noteworthy that the low percentage of DOT implies unfavorable outcomes and, consequently, weaknesses in TB surveillance and control actions.